La suppression de l’impôt de solidarité sur la fortune : réforme économique ou idéologique ? - Pierre Merle (Revue de la Régulation, 2018)
Solidarity tax on wealth is removed in 2018. This major tax reform is supposed to promote investment, economic growth and employment. The socio-economic analysis does not validate the negative effects attributed to this tax, nor the positive effects associated with its removal. The taxation of wealth is not just an economic and fiscal question. It also has effects on the distribution of power and the political organization.